Application of Political Sociology in the Indian Context (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Independence and the establishment of a democratic republic in India gave rise to the field of political sociology inside the country. It became imperative for the social science fields, particularly sociology and political science, to comprehend not just how contemporary political institutions work, but also how the conventional social fabric of Indian society would adapt to this new political order, in light of this seismic shift. This unique focus on society within Indian political theory is what ultimately led to the development of political sociology. Many Indian sociologists and social scientists set out in the years after India's independence to decipher the shifting social milieu in which political conduct was taking place. A new field of study called political sociology was necessary due to the complex nature of the landscape at the intersection of politics and society. Regardless, the importance of both sociology and political science remained unabated, especially because political sociology emerged as a branch of sociology, despite their close relationship. Examining the work of Dipankar Gupta, this article delves deeply into the history of political sociology in India. His work illuminates the pre- and post-independence social and political climates, as well as the ways in which both the traditional and contemporary values that were embraced thereafter were able to coexist.